A novel bypass-gas metal arc directed energy deposition for in-situ synthesis Al–Cu–Li alloy: exploring the microstructure and mechanical properties evolution from as-deposited state to T6 state - Fenglei Cao; Dianlong Wang; Yunfei Gu; Jiajia Shen; Ziwei Bai; Zhen Tan; Zhimin Liang; Zhenzhen Peng; Xiao Yang; Shaohui Chen; Zhi Zeng; Liwei Wang; et al. (Virtual and Physical Prototyping)
A novel bypass-gas metal arc directed energy deposition (bypass-GMA DED) was proposed to prepare high strength Al–Cu–Li-based components. An Al–5.51Cu–0.48Li alloy was successfully prepared, followed by subsequent T6 treatment. The microstructure evolution and improvement of mechanical properties after the T6 state were benchmarked against the as-deposited condition. The component fabricated by bypass-GMA DED has obvious periodic distribution characteristics, with a large number of fine equiaxed grains distributed near the interlayer fusion boundary and coarse columnar grains within the intralayer region. After heat treatment, the Al–5.51Cu–0.48Li alloy is mainly composed of four types of strengthening phases, θ′, θ″, δ′ and T1, which contrasts with the sole presence of θ phase in the deposited condition. These phases are conducive to the improvement of mechanical properties. The strength of the prepared alloy is higher than those additively manufactured Al–Cu–Li alloys, reaching values similar to those of conventional third generation Al–Cu–Li alloys.